Penyuluhan dan Edukasi Resistansi Antibiotik pada Mahasiswa Gizi di Sekolah Tinggi Ilmu Kesehatan Adila Kota Bandar Lampung - Made Laksmi Meiliana; Indah Ana Resti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Antibiotic resistance is a global health problem that requires international efforts to prevent the ineffectiveness of existing antibiotics and support the development of new antimicrobial agents. The increasing use of antibiotics in the community must be accompanied by proper understanding regarding rational antibiotic use to minimize the risk of resistance. This community service activity aimed to provide education on rational antibiotic use and the dangers of antibiotic resistance to undergraduate nutrition students at STIKes Adila, Bandar Lampung. The activity was conducted through educational sessions using flyers, presentation slides, and interactive discussions to encourage active participation and improve understanding of the topic. Evaluation was carried out using pre-test and post-test assessments to measure changes in participants’ knowledge levels. Descriptive analysis showed an improvement in participants’ knowledge, with the high knowledge category increasing from 0% during the pre-test to 85% in the post-test, while the low knowledge category decreased from 35.5% to 0% after the intervention. These findings indicate that educational interventions can effectively enhance awareness and understanding of rational antibiotic use and the prevention of antibiotic resistance. Therefore, continuous educational programs are important to promote responsible antibiotic use and support public health efforts in combating antibiotic resistance.